PELATIHAN DIGITAL MARKETING UNTUK MENINGKATKAN KAPASITAS PENJUALAN UMKM OTAK-OTAK BANDENG - Rita Nataliawati; Umar Yeni Suyanto; Ika Purwanti; Mesra Berlyn Hakim; Maretha Anggraini; Putri Nur Sholekha; Nur Aliyah (Jurnal Abdimas Bina Bangsa, 2023)
The main problem faced by MSMEs in Menganti Village, Glagah District, Lamongan Regency is in terms of product marketing. There is still a lack of knowledge and skills of MSMEs in using online markets, making marketing of MSME products still limited. Training and mentoring activities by a team of lecturers and students aiming to help partners utilize their gadgets as product marketing tools and optimize online marketing to increase sales turnover using the TikTok application. The training was held on 9 September 2022 at the Glagah District Office, Lamongan Regency with 10 training partners. Implementation of the training contains an explanation of the reasons for using TikTok, explanation of material on how to create an account on TikTok, upload product photos/videos, add music and promotional narratives to product photos/videos, trainees practice creating accounts on TikTok accompanied and guided by the committee. It is hoped that from this training activity, MSME actors in Menganti village, Glagah Sub-District, will have basic knowledge and skills on how to expand product marketing, which in turn can increase the sales capacity of milkfish brains